Myoinositol: A new marker of intrauterine growth restriction?. (November 2013) - Dessì, A.; Fanos, V.
Abstract : Inositol is a cyclic sugar alcohol which occurs naturally in a variety of stereoisomers, the most common of which is myo-inositol. Inositol phosphoglycan molecules have been isolated from mammalian tissues and are a major component of the intracellular mediators of insulin action. The fetus with intrauterine growth retardation (IUGR) activates a series of adaptive mechanisms to increase the chances for survival, such as a saving of glucose to ensure nutrition of the vital organs, with a consequent reduction in insulin secretion. It can be hypothesized that the reduced production of fetal insulin leads to an excretion of inositol from the intracellular to the extracellular compartment, with a consequent increase of the metabolite in plasma and urine and a decrease inside the cells. Recently, reports suggesting that the increase in extracellular myo-inositol may be a valid marker of an altered glucose metabolism during fetal development in IUGR have been published.